Metallocene supported on porous and nonporous polyurethane particles for ethylene polymerization. Issue 4 (27th November 2013) - Dorresteijn, Robert; Nietzel, Sven; Joe, Daejune; Gerkmann, Yi; Fink, Gerhard; Klapper, Markus; Müllen, Klaus
<x xml:space="preserve">Abstract</x> Micrometer‐sized spherical polyurethane supports with a narrow size distribution and adjustable porosity were synthesized via the nonaqueous emulsion polymerization technique. They can be directly used in metallocene‐catalyzed olefin polymerization, preventing complex aggregation procedures that are typical for other organic and inorganic supports based on silica or latex particles. The reasonable catalytic activity and study of fragmentation behavior, using various optical techniques, demonstrates the potential applicability of the supports. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>